MACC1 ablation suppresses the dedifferentiation process of non-CSCs in lung cancer through stabilizing KLF4 - Zhuoshi Li; Shiqing Wang; Tao Guo; Xinyi Yan; Chaoqun Chen; Wenjing Zhang; Jinyao Zhao; Jinrui Zhang; Shilei Zhao; Yang Wang; Yangfan Qi; Chundong Gu (Cell Death Discovery)
Abstract Metastasis-associated in colon cancer-1 (MACC1) was identified as a new player in lung cancer development, and some stemness-related genes can be novel transcriptional targets of MACC1. Cancer stem cells (CSCs) are responsible for sustaining tumorigenesis and plasticity. Both CSCs and non-CSCs are plastic and capable of undergoing phenotypic transition, especially the dedifferentiation of non-CSCs switch to CSC-like cells. However, the precise role of MACC1 during this process is largely unknown. Here, we showed that MACC1 promoted the transition from non-CSC to CSC in lung cancer. We found MACC1 was overexpressed in stemness enriched cells, enhancing the transition from no-CSCs to CSCs, while short-hairpin RNA-mediated Knockdown of MACC1 impaired this process. High-throughput sequencing and tumor specimen analysis revealed that MACC1 was negative correlated with Krüppel-like factor 4 (KLF4) expression level, which acts as a negative stemness regulator in lung cancer. Mechanistically, MACC1 delays the degradation of KLF4 mRNA by repressing the expression of microRNA-25, thereby promoting the KLF4 mRNA stabilization at the post-transcriptional level. Collectively, our findings may facilitate efforts to promote the development of precision targeted therapy for cancer stem cells in lung cancer.